APPLICATION OF CALCULATION GROSS TONNAGE (GT) AND NET TONNAGE (NT) FISHING BOAT SYSTEM BASED ON WEB - Patrialis Akbari; Ronald M Hutauruk; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstrackThis research was conducted month december 2014 - february 2015 in the laboratory of Fishing boat. The research purpose is to design an application that is easy to use in the calculation of tonnage of fishing boat, namely gross tonnage (GT) and net tonnage (NT). The method used is descriptive method. The results showed that with this application can determine the size of the tonnage of the boat is gross tonnage (GT) and net tonnage (NT) are approaching the actual size easily, quickly and clearly. After validating the data from department of fisheries and marine, obtained difference calculation accuracy by 5 %, so the application can be applied in the calculation tonnage fishing boat. The application can be used for data collection boat owners and taxation. The application can be used by fishermen, government and student fisheries.Keywords : Application, Tonnage, Fishing boats